Zum Auftreten der Mykosen bei Stechmücken in Mähren (Diptera: Culicidae). - Novák, Dušan (Contributions to Entomology = Beiträge zur Entomologie, 1965)
Gnats (Culex pipiens Linnaeus) in the March piain round Hodonin are greatly infested with the fungus Entomophthora conglomerata Sorokin, while no such attacks were observed in the Beskids. In certain places up to 100 per cent, of the gnats die each year. The extent of the attack varies in the zone between these two localities. The disease does not appear sporadically with long intervals; it is a continual epizooty.